Faktor Risiko Stunting pada Bayi dan Balita (Anak Usia 0-59 Bulan) di Wonosobo - Fibrinika Tuta Setiani; Abdullah Azam Mustajab (Malahayati Nursing Journal, 2023)
ABSTRACT Stunting is a chronic nutritional problem which results in very short or stunted children's height. Stunting results in increased morbidity, mortality, poor child development, learning capacity, increased risk of infection, non-communicable diseases in adulthood, decreased productivity and economic capacity. The purpose of the study was to determine the relationship between risk factors and the incidence of stunting in the village of Slukatan, Wonosobo. The study used a cross-sectional design with a population of 161 toddlers and 56 toddlers who were stunted. Data analysis used chi square analysis and logistic regression. The results of the chi square analysis showed low birth weight (OR= 4.89), gender (OR= 2.60), exclusive breastfeeding (OR= 3.11), disease (OR= 3.42), economic status (OR= 2.25), mother's education (OR= 3.97) and mother's height (OR=5.61) are risk factors for stunting. The results of the logistic regression test showed that three independent variables were significantly related, such as economic status (OR= 4.05, 95%CI= 1.40-8.90), mother's education (OR= 4.42, 95%CI= 1.49-7.71) and mother's height (OR= 4.98 , 95% CI = 1.60-12.35). There are four variables that are not significantly related, such as low birth weight (OR= 1.52, 95% CI= 0.42-2.33), gender (OR= 1.73, 95% CI= 0.55-1.79), exclusive breastfeeding (OR= 2.30, 95% CI= 0.83 -3.51) and disease (OR= 2.32, 95% CI= 0.84-2.43). The conclusion of research variables such as low birth weight, gender, exclusive breastfeeding, disease, economic status, mother's education and mother's height are risk factors for stunting. Keywords: Infants, Toddlers, Risk Factors, Stunting  ABSTRAK Stunting menjadi permasalah gizi kronik yang mengakibatkan tinggi badan anak sangat pendek atau kerdil. Stunting mengakibatkan morbiditas dan mortalitas meningkat, buruknya perkembangan anak, kapasitas belajar, risiko infeksi meningkat, penyakit tidak menular di masa dewasa, produktivitas dan kemampuan ekonomi menurun. Tujuan penelitian untuk mengetahui hubungan faktor risiko terhadap kejadian stunting di desa Slukatan, Wonosobo. Peneltian menggunakan desain cross-sectional dengan populasi 161 bayi balita dan 56 bayi balita yang mengalami stunting. Analisis data menggunakan analisis chi square dan regresi logistik. Hasil analisis chi square menunjukkan BBLR (OR= 4.89), jenis kelamin (OR= 2.60), ASI eksklusif (OR= 3.11), penyakit (OR= 3.42), status ekonomi (OR= 2.25), pendidikan ibu (OR= 3.97) dan tinggi badan ibu (OR=5.61) menjadi faktor risiko stunting. Hasil uji regresi logistik menunjukkan tiga variabel bebas berhubungan signifikan seperti status ekonomi (OR= 4.05, 95%CI= 1.40-8.90), pendidikan ibu (OR= 4.42, 95%CI= 1.49-7.71) dan tinggi badan ibu (OR= 4.98, 95%CI= 1.60-12.35). Terdapat empat variabel tidak berhubungan signifikan seperti BBLR (OR= 1.52, 95%CI= 0.42-2.33), jenis kelamin (OR= 1.73, 95%CI= 0.55-1.79), ASI eksklusif (OR= 2.30, 95%CI= 0.83-3.51) dan penyakit (OR= 2.32, 95%CI= 0.84-2.43). Kesimpulan variabel penelitian seperti BBLR, jenis kelamin, ASI eksklusif, penyakit, status ekonomi, pendidikan ibu dan tinggi badan ibu menjadi faktor risiko stunting. Kata Kunci: Bayi, Balita, Faktor Risiko, Stunting